Financialisation as a strategic action field: An historically informed field study of governance reforms in Chinese state-owned enterprises. (July 2018) - Modell, Sven; Yang, ChunLei
Abstract: This paper extends extant research on financialisation, which has mainly evolved in advanced capitalist economies, through an historically informed field study of governance reforms in Chinese state-owned enterprises (SOEs). Mobilising the theory of strategic action fields (SAFs), we conceptualise the evolution of such reforms as a protracted framing process where different actors sought to influence the meanings attributed to shareholder-focussed governance practices. We examine how challengers of extant governance practices, such as the World Bank, and incumbent actors representing the interests of the Chinese state vied for influence over governance reforms and how various regulatory bodies, assuming the role of internal governance units (IGUs), enjoyed varying degrees of success in advancing context-specific governance practices. Shareholder-focussed accounting techniques, such as Economic Value Added (EVA™), played an increasingly salient role in this process. Yet, emerging governance practices primarily came to reflect the interests of the Chinese state in maintaining and increasing the value of state assets whilst preserving its political control of SOEs. We contribute to the literature on financialisation by showing how pressures for shareholder value creation can be channelled into governance practices which attenuate the pervasive effects of financialisation in contemporary society. We also contribute to research on accounting in emerging economies by exploring the under-researched role of IGUs in the local adaptation of "Western" governance practices. We discuss how future studies can bring these bodies of research closer together and extend research on financialisation to a wider range of institutional contexts.